Spillovers from high-skill consumption to low-skill labor markets - Francesca Mazzolari; Giuseppe Ragusa (Institute for the Study of Labor (IZA), 2007)
Census data show that since 1980 low-skill workers in the United States have been increasingly employed in the provision of non-tradeable time-intensive services - such as food preparation and cleaning - that can be broadly thought as substitutes of home production activities. Meanwhile the wage gap between this sector and the rest of the economy has shrunk. If skilled workers, with their high opportunity cost of time, demand more of these time-intensive services, then wage gains at the top of the wage distribution (such as those observed in the last three decades) are expected to raise the consumption of these services, consistent with these stylized facts. Using both consumption expenditure data and city-level data on employment and wages of workers of different skills, we provide several pieces of evidence in favor of these demand shifts, and we argue that they provide a viable explanation for the growth in wages at the bottom quantiles observed in the last fifteen years.
Keywords: 330; Service jobs; market substitutes for home production; low-skill employment and wages; wage growth polarization; Dienstleistungsberufe; Hausarbeit; Lohnstruktur; Ungelernte Arbeitskräfte; Gesamtwirtschaftlicher Konsum; Hochqualifizierte Arbeitskräfte; USA